AB0623 RATE AND PREDICTIVE FACTORS ASSOCIATED WITH SUSTAINED REMISSION IN IDIOPATHIC INFLAMMATORY MYOSITIS. (2nd June 2020) - Vojinovic, T.; Gjoni, X.; Fredi, M.; Franceschini, F.; Cavazzana, I.
Abstract : Background: Idiopathic inflammatory myositis (IIM) is a group of heterogeneous connective tissue diseases, characterised by chronic muscle inflammation, myositis-specific or myositis-associated autoantibodies and different extra-muscular features. Achieveing low disease activity or remission in patients with IIM has proven to be difficult due to the wide clinical spectrum of the different IIM types. Objectives: To retrospectively assess any predictive factors for sustained remission in IIM patients Methods: We retrospectively analyzed data taken from medical charts, which included age at disease onset, gender, laboratory data as well as clinical features present at onset, organ involvement and treatment history. A total of 151 adult patients with IIM followed-up for > 1 year were retrospectively enrolled. Remission was defined as no clinical and laboratory evidence of disease activity persistent for more than 6 months during follow-up, while undergoing myositis therapy or under no medication. The remission of cutaneous involvement was defined as no current activity of skin rash, absence of Gottron's papules as well as heliotrope rash and erythema, whereas the remission of pulmonary involvement was considered as no requirement for intensification of immunosuppressive therapy during follow-up. Likewise, absence of muscle weakness or hyposthenia was taken into account for evaluating muscle involvement. Moreover, the clinical features were accompanied by normalization of myogenic enzymes such as creatine kinase (CK) and lactate dehydrogenase levels. Results: Among all 151 patients, 89 (58.9%) patients achieved sustained remission. By univariate analysis, overlap myositis (7.9% vs 27.4%; p=0.003; OR:0.22), cancer-associated myositis (CAM) (7.8% vs 19.35%; p=0.046; OR:0.3), as well as the presence of anti Ku (3.37% vs 12.9%; p=0.05; OR:0.23) and anti TIF-1 gamma (1.1% vs 8%; p=0.043; OR:0.13) antibodies and polyarthritis (11.2% vs 24.19%; p=0.045; OR: 0.397) at onset were significantly associated with active IIM, not achieving remission. Out of 89 patients in remission, 79 (88.8%) achieved long-term sustained remission, lasting at least 2 years, whereas 10 patients (11.2%) showed relapse. Most of relapsed patients showed a relapse/remitting disease, with no evident trigger for the relapse. We divided our cohort of 89 patients in remission in 2 subsets: 83 patients in remission undergoing therapy (93.3%) and 6 patients in drug-free remission (6.7%). No significant differences were found between two groups, except for younger age at onset (p=0.0002) found in patients achieving drug-free remission. Conclusion: Sustained remission occurs in about one half of patients with IIM. The presence of anti Ku and anti TIF-1 gamma antibodies as well as polyarthritis at onset lowers the chance of achieving sustained remission. Younger age at diagnosis has proved to predict drug-free long-lasting remission. Disclosure of Interests: None declared